Coating binders based on structured self-crosslinking latexes - Rückerová, Adéla; Machotová, Jana; Kalendová, Andréa; Puková, Kateřina (Česká společnost průmyslové chemie, 2016)
This work is focused on self-crosslinking latexes synthesized by the technique of emulsion polymerization. The prepared water dispersions of acrylic copolymers contain microgel particles of core-shell structure. The variability of properties of the resulting latexes is the advantage of this type of coating binders. Crosslinking ensuring the microgel structure of latex particles was achieved by hexaallylamino-cyclo-triphosphazene which also aims to reduce the flammability of the resulting polymer.
Pojiva pro nátěrové hmoty na bázi strukturovaných samosíťujících latexů
Keywords: Latex; coatings; phosphazene; Latex; nátěrové hmoty; fosfazen